Knowledge of the Adverse Effects of Smoking and Related Changes in Smoking Status during Pregnancy among Female Smokers - Purev, Odonchimeg; Enkhjargal, Manduul; Oidov, Batgerel; Luvsandagva, Baigalmaa; Dashtseren, Myagmartseren; Ogawa, Shota; Hayashi, Kunihiko; Tsushima, Yoshito; Shinozaki, Hiromitsu (Central Asian Journal of Medical Sciences, 2023)
No abstract in English